Feast for 10 - Falwell, Cathryn (New York : Clarion Books, 1993)
Numbers from one to ten are used to tell how members of a family shop and work together to prepare a meal.
Maine author.
Keywords: Counting; African Americans -- Juvenile fiction; Cookery -- Juvenile fiction; Families -- Juvenile fiction